Attitude towards sex offenders : an Icelandic sample of psychology students and the general public - Sara Björgvinsdóttir 1992- (2016)
This study explores attitude towards sex offenders in an Icelandic population. A questionnaire was administered both online and via paper and pencil. The written survey was given to psychology students at Reykjavík University (N = 78). For the general public the survey was administered online (N = 92). The total number of participants was 170, 128 females and 42 males. The Attitude Towards Sex Offender scale (ATS) was used to explore the participants’ attitude toward sex offenders. This study’s aim was to see if there was any; 1) gender difference, 2a) difference between victim type (vignette), 2b) gender difference within vignettes, 3) difference between the general public and psychology students and 4) difference between those who had been sexually abused or knew of someone who had been sexually abused and those that had not, in attitude towards sex offenders. An independent t-test found no significant difference in the average ATS scores between those variables however there was a significant 5) difference between first and second year psychology students. Second year students held a more positive attitude towards sex offenders than first year students. Keywords: attitude, sex offenders, vignette, psychology students, general public. Rannsóknin skoðar viðhorf Íslendinga til kynferðisafbrotamanna. Notast var við rafræna og skriflega spurningakönnun. Nemendur við sálfræðideild Háskólans í Reykjavík (N = 78) tóku könnunina skriflega og almenningur (N = 92) tók könnunina rafrænt. Þátttakendur voru í heildina 170, 128 konur og 42 karlar. Attitude Towards Sex Offenders (ATS) skalinn var notaður til þess að mæla viðhorf þátttakenda til kynferðisafbrotamanna. Markmið rannsóknarinnar var að skoða; 1) kynjamun, 2a) mun á milli vignette, 2b) kynjamun innan vignette, 3) mun á milli sálfræðinema og almennings, 4) mun á milli þeirra sem annaðhvort hafa orðið fyrir kynferðisofbeldi eða þekkja einhvern nákominn sem hefur orðið fyrir kynferðisofbeldi og þeirra sem gera það ekki, á viðhorfum til kynferðisafbrotamanna. ...